Efficient adsorption behavior of phosphate on La-modified tourmaline. Issue 1 (March 2015) - Li, Guoting; Chen, Dong; Zhao, Weigao; Zhang, Xiwang
Abstract Natural mineral tourmaline is an intelligent material with a great potential application for water purification. In this study, tourmaline was modified by La(III) via a simple ion exchange process for high efficient phosphate adsorption. EDX analysis demonstrated the atomic ratio of La(III) in the La-modified tourmaline was 4.6%. SEM analysis indicated that the exhausted adsorbent particles aggregated seriously after phosphate adsorption, becoming more compact. Concurrently, the surface area of La-modified tourmaline increased from 2.19 m2/g (raw tourmaline) to 15.59 m2/g after immobilization of La(III). Efficient phosphate adsorption was achieved by the modified sorbent in a wide pH range, even in alkaline solution. Over 90.0% of phosphate adsorption occurred within the initial 15 min, revealing that it was the fast adsorption process, which is beneficial for practical water purification. Pseudo-second-order kinetic model was proved to fit the kinetic data, which indicates phosphate adsorption might be a chemical sorption. The maximal adsorption capacity for phosphate was 108.7 mg/g at 298 K and neutral pH solution, which is higher than those of most other sorbents reported so far. Isotherm and thermodynamic analysis indicated that phosphate adsorption was spontaneous and exothermic. The prepared sorbent proved to be capable of controlling the solution pH to near neutral pH conditions.